Where to Publish? Analysis of the Supply of Argentine Journals in Psychology and Related Sciences (Updated December 2024) (Revista de Psicología, 2025)
Where to Publish? Analysis of the Supply of Argentine Journals in Psychology and Related Sciences (Updated December 2024)